2019
DOI: 10.1177/2050312119825509
|View full text |Cite
|
Sign up to set email alerts
|

The impact of body mass index on resource utilization and outcomes of children admitted to a pediatric intensive care unit

Abstract: Introduction:Obesity is associated with poor health outcomes but may be protective in intensive care unit patients. The objective of this study is to describe the characteristics of underweight, normal weight, and obese children, and to compare their length of stay, resource utilization, and mortality.Methods:The charts of 1447 patients who were admitted to a tertiary-level pediatric intensive care unit during 1 calendar year were reviewed. Patients were divided into three groups: underweight (<5th percentile)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Classification of the study population based on patients' BMI showed that they had a normal weight (61.5%). A similar outcome has been reported by Kamal Sharma et al [11], in which patients with normal weight were also dominant (61.5%). This may suggest that there is not a significant difference in the risk of occurring infectious diseases between underweight, normal weight, and obese children.…”
Section: Discussionsupporting
confidence: 88%
“…Classification of the study population based on patients' BMI showed that they had a normal weight (61.5%). A similar outcome has been reported by Kamal Sharma et al [11], in which patients with normal weight were also dominant (61.5%). This may suggest that there is not a significant difference in the risk of occurring infectious diseases between underweight, normal weight, and obese children.…”
Section: Discussionsupporting
confidence: 88%
“…Children in the critical care unit are at risk of having their nutritional status deteriorating due to their disease or barriers to nutrient delivery ( 43 ), further worsening their prognosis ( 42 ). Appropriate nutritional interventions for UN patients can decrease their incidence of mortality, which is similarly found in the study by Sharma et al ( 33 ); the intervention group had a decreased mortality incidence as a result of appropriate nutritional interventions.…”
Section: Discussionsupporting
confidence: 69%
“…The forest plot was described as having UN cases significantly decreased mortality incidence in two studies ( 27 , 37 ), while four out of eleven studies described increased significance in mortality incidence on UN children, which was between 3 and 18 percentiles ( 24 , 28 , 30 , 33 ); for more details, refer to Figure 2A .…”
Section: Resultsmentioning
confidence: 99%
“… 7 Sharma et al also reported pediatric intensive care units and hospital lengths of stays were higher in underweight children, and underweight children were younger when compared to normal or obese children. 23 On the other hand, a study done in hospitalized pediatric patients aged 2 to 18 years showed obese patients had 15% longer hospital stays and 19% higher hospital costs than normal weight patients, when controlled for age, sex, ethnicity, insurance type, calendar year, and primary diagnosis. 24 This U-shaped curve was also reported in mortality rate in pediatric intensive care units with respect to weight centile, and the lowest mortality rate was around 75th weight-for-age centile.…”
Section: Discussionmentioning
confidence: 99%